DEVELOPING A MODEL OF ENGLISH INSTRUCTIONAL MATERIALS USING ENGLISH FOR SPECIFIC PURPOSE (ESP) APPROACH FOR INFORMATION SYSTEM (SI) STUDENTS OF STMIK PALANGKA RAYA - Rahmah, Miftahul; Usadiati, Wahjuningsih; Karani, Elanneri (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2019)
The lecturers of STMIK Palangka Raya were given the autonomy in developing the curriculum and syllabus of English subject so they must use English instructional material that related with the developed curriculum and syllabus. So that, the writer was interested in developing English instructional material and considering English for specific purpose as the approach in developing the material. The topics of the developed English instructional materials were about computer and technology. The subject of this R &D study was the Information System (SI) students of STMIK Palangka Raya. The research accomplished through the procedures of need analysis, first draft material development, expert validation, materials revision, material try out and final draft of material revision. The instrument used in this study consisted of observation, questionnaire and guided interview for the students, lecturers and also the expert validation. The data obtained were analyzed and described qualitatively. The result of the need analysis showed that the students were in the need of English Instructional Materials which were relevant to their major content course and their level of English proficiency. Related to this condition, the materials taken from some English for computer user books and some related websites. The data of try out showed that the effectiveness of the developed material in teaching learning process during try out, the observation and interview reflected that the students were very interested about the latest English Instructional Materials and they got involve actively in teaching learning process.